The Cyborg Affect: Encountering Via Switch - Fornssler, Barbara (eTopia, 2010)
This paper is the presentation of a new thinking toward the idea of “encounter” in relation. Following the emphasis on encounter—that is, a form of situating relation in communication and culture—I would like to summarize the idea of “switch” and expand this thinking toward a new consideration of our relationship with technology. This contributes to understanding relation and encounter in affective and not effective terms. If relation is affective, embodied in both technology and ourselves (if we should make such distinctions), then this changes our conception of the encounter, what it means, and how it can be applied toward creating new theoretical terrain